Do Adversity Intelligence have Roles in Career Maturity for Accounting Pre-Service Teacher? - Susilowati, Nurdian; Aeni, Ida Nur; Mudrikah, Saringatun (Fakultas Ekonomi, Universitas Negeri Semarang, 2021)
This study aims to analyze the effect of ICT skills and English competencies on career maturity with adversity intelligence as a moderating variable. This study was conducted on accounting pre-service teacher students. The study population is eighty students of accounting education international class. By using simple random sampling, there were sixty-five students as the research sample. Data are collected by questionnaire and analyzed using descriptive analysis and moderation regression analysis (MRA). The results show that ICT skill does not have a significant effect on career maturity. English competencies have a significant impact on career maturity. Adversity intelligent moderate ICT skill on career maturity. Adversity intelligence moderates English competencies on career maturity. English competencies have an essential role in career maturity, which will further affect his career choices. The performance of adversity intelligence as the intelligence behind success in facing challenges after failures many are explored and investigated in the world of education today. Adversity intelligence is needed to deal with various difficulties experienced in learning.